2023
DOI: 10.1177/1358863x221140151
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and regional trends of peripheral artery disease-related mortality in the United States, 2000 to 2019

Abstract: Introduction: Peripheral artery disease (PAD) is a common progressive atherosclerotic disease associated with significant morbidity and mortality in the US; however, data regarding PAD-related mortality trends are limited. This study aims to characterize contemporary trends in mortality across sociodemographic and regional groups. Methods: The Centers for Disease Control and Prevention Wide-Ranging OnLine Data for Epidemiologic Research (CDC WONDER) was queried for data regarding PAD-related deaths from 2000 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…They also identified that men, Black Americans, and those in rural counties had the highest adjusted mortality rates. 10…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They also identified that men, Black Americans, and those in rural counties had the highest adjusted mortality rates. 10…”
mentioning
confidence: 99%
“…8 This higher risk of PAD-related mortality is shown in the work of Dicks et al, 9 where utilizing NHANES data found that Black individuals presented with more premature PAD, had a higher burden of SDoH, and those with concomitant coronary artery disease (CAD) had higher rates of age-adjusted mortality compared to their White counterparts. 9 Issa et al 10 show us that PAD-related mortality has decreased over the last two decades, with a plateau over the last several years. They also identified that men, Black Americans, and those in rural counties had the highest adjusted mortality rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation